1994
DOI: 10.1128/jcm.32.11.2749-2754.1994
|View full text |Cite
|
Sign up to set email alerts
|

RTX toxin genotypes and phenotypes in Actinobacillus pleuropneumoniae field strains

Abstract: Actinobacillus pleuropneumoniae serotype reference strains and 204 A. pleuropneumoniae field strains representing all 12 serotypes and both biovars 1 and 2, obtained from laboratories from various countries worldwide, were analyzed for the presence of the toxin genes apxIC, apxIA, apxIB, apxID, apxIIC, apxIIA, apxIIIC, apxIIIA, apxIIIB, and apxIIID by DNA-DNA hybridization with specific gene probes. Expression of the toxins ApxI, ApxII, and ApxIII was assessed by immunoblot analysis with monoclonal antibodies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 30 publications
2
49
0
2
Order By: Relevance
“…Previous studies suggested that these cross-reactions can be primarily attributed to shared species-specific antigens such as lipopolysaccharide or membrane proteins (Perry et al, 1990). In our study, the distribution of the apxI and apxIII operon was in agreement with that presented in the previous report (Beck et al, 1994), and these operons have been shown to play the roles of immune-protective antigens (Du et al, 2008). However, this is the first report on the distribution of other differential genes (the encoded proteins are listed in Tables 3 and 4).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies suggested that these cross-reactions can be primarily attributed to shared species-specific antigens such as lipopolysaccharide or membrane proteins (Perry et al, 1990). In our study, the distribution of the apxI and apxIII operon was in agreement with that presented in the previous report (Beck et al, 1994), and these operons have been shown to play the roles of immune-protective antigens (Du et al, 2008). However, this is the first report on the distribution of other differential genes (the encoded proteins are listed in Tables 3 and 4).…”
Section: Discussionsupporting
confidence: 92%
“…Serotype 3 has been known to contaminate pig farms in Finland, but it has not caused acute epidemics. This is typical for serotype 3 strains, which have previously been shown to be less pathogenic in certain areas (NIELSEN, 1982;NI(:oL~:T, 1992;Mot R et al, 1992;BECK et al, 1994). Variation in the virulence of serotype 2 strains has also been reported.…”
Section: Discussionmentioning
confidence: 59%
“…Pigs that survive A. pkumpneumoniae infection often become subclinical carriers of the bacterium (NIELSEN, 1982). A. pkumpneumoniae can be differentiated into 12 serotypes and into two biovars (biovar 1, NAD dependent, biovar 2, NAD independent) (NIFLSEN, 1986;BECK et al, 1994). Serology and serotyping are the most important tools in epidemiology and sanitation programmes to control swine pleuropneumonia (NICOLET, 1992;BECK et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normally, serovars 1-12 and 15-16 are biovar 1, and serovars 13 and 14 are biovar 2. However, some biovar 2 isolates belonging to serovars other than 13 and 14(Beck et al, 1994;Dom & Haesebrouck, 1992;Maldonado, Valls, Mart ınez, & Riera, 2009), as well as a biovar 1 serovar 13 isolate(Perry et al, 2012), have been identified. Additionally, some untypable isolates have been reported(Ito, Ogawa, Fukamizu, Morinaga, & Kusumoto, 2016;Kokotovic & Angen, 2007).…”
mentioning
confidence: 99%